Evaluation of Cytopathological Techniques for the Diagnosis of Canine Visceral Leishmaniosis with Lymph Node Samples. (October 2019) - Guerra, J.M.; Fernandes, N.C.C.A.; Réssio, R.A.; Magno, J.A.; Kimura, L.M.; Barbosa, J.E. de R.; Bertollo, D.M.B.; Taniguchi, H.H.; Hiramoto, R.M.; Motoie, G.; Tolezano, J.E.; Cogliati, B.
Summary: The identification of the parasite in cytological smears of lymph node aspirates is a widely applied technique for the direct diagnosis of Leishmania spp. infection, especially in endemic areas. Although very specific, this method has limited sensitivity, and improving the technique would be highly desirable. This study aimed to evaluate the efficacy of conventional smear cytology (SC), liquid-based cytology (LBC), cell block (CB) stained with haematoxylin and eosin (HE) and immunocytochemistry (ICC), and formalin-fixed paraffin wax-embedded tissue immunohistochemistry (FFPE–IHC) compared with serology and polymerase chain reaction for the diagnosis of canine visceral leishmaniosis (CVL) in lymphoid tissue. The use of a preservative medium and centrifugation for cytological samples reduced the number of unsatisfactory artefacts/background. Moreover, LBC allowed excellent cellular preservation and the application of ancillary techniques, such as CB and ICC. SC was the most accurate morphological diagnostic method (45.0%). CB–ICC alone or associated with SC demonstrated significantly higher sensitivity (70.0% and 72.0%, respectively) when compared with SC alone (34.00%). CB–ICC was found to be more effective in the detection of infected animals with mild clinical signs, similar to FFPE–IHC. The specificity and positive predictive value were similar between all methods. Finally, the detection limit for CB–ICC and SC + CB–ICC was identical (18.46 amastigotes/mm 2 ). Our study suggests that CB–ICC is a promising tool for improvement of the cytopathological diagnosis of CVL and may be applied in routine epidemiological screening.